2014
DOI: 10.1017/s1049023x14000132
|View full text |Cite
|
Sign up to set email alerts
|

A Paramedic Field Supervisor's Situational Awareness in Prehospital Emergency Care

Abstract: Paramedic field supervisors are multitasking persons, building SA by using the available data, combining it with extensive know-how from their working methods and competencies, and their tacit knowledge. The results can be used in developing work processes, training programs, and information systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…The most common reason, according to respondents of this study, was care providers' assessment of the patient's situation. [16] As regards psychosocial reasons as a background for non-conveyance, the findings are consistent with earlier research, which states that the emergency team is sometimes only called "to be on the safe side". In many cases the patient does not require transport to hospital [12,20] or cannot be considered a client of emergency care services.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The most common reason, according to respondents of this study, was care providers' assessment of the patient's situation. [16] As regards psychosocial reasons as a background for non-conveyance, the findings are consistent with earlier research, which states that the emergency team is sometimes only called "to be on the safe side". In many cases the patient does not require transport to hospital [12,20] or cannot be considered a client of emergency care services.…”
Section: Discussionsupporting
confidence: 88%
“…The finding brings into mind the importance of gaining correct and adequate patient information to support decision-making. [16] Earlier, a doctor's assessment and decision has been described as the reason for non-transportation. [12] It has also been repeatedly confirmed that emergency care providers' work is characterized by hurry and stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bearing in mind that a research should not interfere the often hectic work of Emergency Response Centre operators it would, however, be extremely difficult to monitor real-life situations so closely that adequate research data could be gathered. The method applied in this study had been tested in previous studies with both PFS and emergency medical dispatchers (Norri-Sederholm et al, 2014a, 2014b. The progressive scenarios had turned out to be realistic and responding to the needs of scientific inquiry.…”
Section: Limitationsmentioning
confidence: 99%